Villous Adenoma of Papilla of Vater - SR Choudhury; AK Malik; Y Chawla; JD Wig (Canadian Journal of Gastroenterology)
Biliary obstruction due to a benign villous adenoma of the ampulla of Vater treated by transduodenal local excision and sphincteroplasty is reported. Local surgical resection enabled a submucosal resection of the adenoma.